Характеристика оселищ проектованої памʼятки природи «Криниця в Гаєвичах» - Потапчук, А. М.; Хом’як, І. В. (НУБіП України, 2025)
Abstract. The designed monument is located in the Ovrutskyi urban united territorial community of Zhytomyr region. Its habitats belong to 13 classes, 16 orders, 20 unions, 26 associations according to the Brown Blanke classification. This diversity is the basis for maintaining a stable ecological balance and preserving local ecosystems. Due to this wealth of plant communities, the reserve becomes an important object for research and monitoring of changes in biodiversity under anthropogenic influence.
Habitat characteristics of the designed natural monument "Krynytsia in Hayevychi"
Keywords: культурна спадщина; природні екосистеми; антропогенний вплив; cultural heritage; natural ecosystems; anthropogenic influence